Penanaman Nilai Tauhid dan Pembentukan Karakter Anak dalam Perspektif Al Qur’an dan As Sunnah - Aceng Badruzzaman; Kisanda Midisen; Wira Syuhada (Jurnal Dirosah Islamiyah, 2025)
Instilling the value of monotheism in children from an early age is the main foundation in forming a strong and religious character. From the perspective of the Qur'an and As-Sunnah, monotheism education not only introduces the concept of divinity, but also instills ethical values, spirituality, and social responsibility. This article aims to examine in depth the concept of monotheism instillation in children's character formation based on an interpretive approach to Surah Luqman verses 13 and an analysis of the hadiths of the Prophet Muhammad. This research uses a literature study method. The results show that monotheism education can shape the character of children who are noble, spiritually resilient, and able to face the challenges of the times with the provision of faith values. The instillation of monotheism can be done through the methods of mauidzah, hiwar, uswah, ibrah, and amtsal as stipulated in the Qur'an and the Prophet's practice. By strengthening the role of parents, especially fathers, in fostering children through a monotheism approach, children's character will be formed more firmly amidst contemporary moral challenges.